(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The control of the flow of goods is alluded to as logistics, and it comprises all operations that turn raw materials into completed commodities. It entails assertively simplifying an industry’s supply-side activities in increases customer importance and receive a market position. Inter integration is necessary for timely deliveries, and marketing will play a vital role. The task ahead is to try and make this connectivity work. We provide a framework of logistics, as well as practical difficulties and research areas for the future. To exemplify the concepts presented, research papers executed at different businesses but also involving multiple participants of supply chain operations are utilized. In this manner, SCM is worried with general business better operations and marks a new method to top managers and interplay with other stakeholders.